Fiscal Policy and Economic Stability: A Case of Pakistan - Farhan Ahmed; Suman Talreja; Yasir Aman; Govinda Lohana (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
This paper aims to assess the impact of fiscal policy on the economic stability within Pakistan. The findings indicate that the fiscal policy process constitutes the subsequent impact on the GDP, FDI, discount rate and CPI. That is to say, the corresponding expansionary and contractionary fiscal process has a direct and significant impact on the overall productivity, the foreign investment, the interest rates and the inflation process of the state. However, in comparison to these three variables, the exchange rate has an indirect impact and is lesser significant as compared to the other variables. The findings help stakeholders to understand how the overall fiscal policy affects the economic and business cycle of the country and how each individual is affected by the decisions made by the government executives in constituting the fiscal policy.